Integrative Didactic Approaches To The Development Of Communicative Competence In Foreign Language Education - Khakimov, Shamsiddin (TLEP – International Journal of Multidiscipline, 2025)
In contemporary foreign language pedagogy, the development of communicative competence has become a central educational objective, reflecting the shift from knowledge-based to performance-oriented learning paradigms. This article explores four key methodological approaches—activity-based, learner-centered, competency-based, and contextual approaches—that underpin effective communicative competence formation. Each approach represents a distinct dimension of modern didactics, contributing to the holistic development of linguistic, sociolinguistic, and pragmatic abilities. Drawing on both international research and Ahmedova’s (2020) didactic principles, the article emphasizes that the integration of these approaches creates a dynamic, interactive, and learner-responsive environment essential for real communication and intercultural interaction.